The Application of Infrared Thermography in Monitoring Reproduction Physiology Status of Ruminant Due to Heat Stress - Fitra Aji Pamungkas; B P Purwanto; W Manalu; A Yani; R G Sianturi (Indonesian Center for Animal Research and Development, 2020)
Assessment on reproduction physiological parameters of ruminant caused by thermal stress usually uses invasive methods. However, these methods are less accurate because they are subjective, require a significant time and resources, and there are problems in animal welfare. Infrared thermography is one alternative solution that can be used. Infrared thermography is a modern, non-invasive, non-destructive, and safe technique to visualize thermal profile and surface temperature. This paper describes the application of infrared thermography in monitoring reproduction physiology status of ruminant. This method does not require physical contact and allows direct visualisation of temperature distribution so that it can be used as a reference in understanding and evaluating several parameters in livestock.